Green synthesis of glycerol carbonate via transesterification of glycerol using mechanochemically prepared sodium aluminate catalysts. (15th February 2022) - Keogh, John; Deshmukh, Gunjan; Manyar, Haresh
Highlights: Significant effect of the method of catalyst preparation on catalyst stability. Mechanochemically prepared catalysts showed superior catalyst stability. 20 wt% NaAlO2/Al2O3 is the most stable catalyst with 96% glycerol carbonate yield. Al2O3 provided highest catalyst stability compared to other metal oxide supports. Abstract: Glycerol, an important by-product from biodiesel production, has significant potential as platform chemical with several different pathways of value addition being investigated. Herein, we report the synthesis of glycerol carbonate via the transesterification of glycerol with dimethyl carbonate using supported sodium aluminate catalysts. The effects of catalyst preparation method, and different metal oxide supports were investigated. Mechanochemically prepared catalysts were more stable than the corresponding catalysts prepared using a wet impregnation technique. Alumina as a support was found to provide the highest level of stability, amongst the metal oxide supports tested. The mechanochemically prepared catalyst with a sodium aluminate loading of 20 wt% supported on alumina, was found to be the most effective catalyst achieving 96 % yield of glycerol carbonate after 60 min. The catalysts were thoroughly characterized to investigate the effect of the catalyst synthesis method on the catalyst structure, catalytic activity and stability. Mechanochemically prepared 20 wt% sodium aluminate supported on alumina showed facile recovery and good reusability over four times with only a marginal decrease in activity.